Effects of Mind–Body Exercises on Schizophrenia: A Systematic Review With Meta-Analysis - Wei, Gao-Xia; Yang, Lin; Imm, Kellie; Loprinzi, Paul D.; Smith, Lee; Zhang, Xiangyang; Yu, Qian (Frontiers in Psychiatry, 2020)
Background: Mind-body exercises (MBEs) have been widely accepted as a complementary therapy for the patients with low exercise tolerance. Currently, the number of experimental studies investigating the effect of MBEs for improving symptoms in people with schizophrenia is increasing. However, results are inconsistent. Methods: We systematically reviewed and meta-analyzed the effects of mind-body exercises on schizophrenia. Seven electronic databases (Pubmed, Web of Science, PsycINFO, Embase, Cochrane Central Register of Controlled Trials [CENTRAL], CNKI and Wangfang) were screened through October 2019 and risk of bias of included studies were assessed in Review Manager 5.3. Results: Meta-analysis on 13 studies with 1159 patients showed moderately significant effects in favor of mind-body exercise intervention to improve positive symptoms (SMD = 0.31; 95% CI 0.01 to 0.60; p = 0.04), negative symptoms (SMD = 0.37; 95% CI 0.14 to 0.60; p = 0.002) and depression (SMD = 0.88; 95% CI 0.63 to 1.13; p＜0.00001). Meta-regression analysis revealed that the improvement in positive symptoms was positively associated with the frequency of intervention (p = 0.04) while a marginally significant correlation was observed between the improved negative symptoms and duration of each session (p = 0.06). Conclusions: This meta-analysis supports the therapeutic effects of MBEs to aid in the treatment of schizophrenia. Further studies need to incorporate rigorous design and large sample size to identify the optimal type and dose of mind-body exercise to inform clinical practices on MBEs recommendations for the management of schizophrenia symptoms.